RempahRise: Transforming TOGA into a Modern Herbal Drink Business Based on a Women's Community - Krisnawati Setyaningrum Nugraheni; Dyah Palupiningtyas; , Aletta Dewi Maria; Khanea Biru Setiawan (Institut Teknologi dan Bisnis Semarang, 2026)
Community empowerment through the utilization of medicinal family plants (TOGA) presents a strategic opportunity to enhance women's economic independence in Indonesia. This community service program, RempahRise, aims to transform TOGA cultivation into modern herbal beverage products within the PKK RW 04 community group at Green Semesta Housing, Ngaliyan District, Semarang. The program employed a participatory action approach across five implementation stages: community observation and needs mapping, herbal beverage processing training, packaging and branding workshop, business management training, and monitoring and evaluation. A total of 20 participants were involved over approximately three months. Pre-test and post-test measured competency improvements across five aspects: TOGA knowledge, processing skills, packaging and branding understanding, digital marketing, and entrepreneurial mindset. Results indicated a mean score increase from 50 to 84.4, reflecting an average improvement of 68.8%. The highest gain was in processing skills ( 88.9%), while the lowest was in TOGA knowledge ( 57.7%). Four herbal beverage variants were developed: Es Telang Coco, Sparkling Ginger Pandan, Ginger Latte Rempah Creamy, and Serai Clove Spice Brew, each accompanied by documented SOPs, food-grade packaging, and an active community brand identity with social media presence. Participant satisfaction reached approximately 85%. The program contributes to SDGs Goals 3, 5, 8, and 12, and demonstrates that structured community empowerment can effectively bridge TOGA's potential with women's economic participation.